Excerpt from Remarks Given at the International Women’s Forum Lunch - Ginsburg, Ruth Bader (Columbia Journal of Gender and Law, 2000)
Turning from advice, I would like to devote the remainder of my brief time with you to an account of what it means to me to be–as I am often billed, and as indeed I am, and as I expect all people here are-a feminist. I had the good fortune to be alive and a lawyer in the late 1960s when, for the first time in history, it became possible to urge before courts, successfully, that society would benefit enormously if women were regarded as persons equal in stature to men. In my college years, 1950- 1954, it was widely thought that women were not suited for many of life’s occupations-lawyering and bartending, banking and brokering, military service, foreign service, piloting planes, jury service, tenured positions at universities, to take just a few of many examples that now seem ancient. So much has changed for the good since then. But there are still too many people who regard feminism with suspicion, people who are discomforted by the very word, even people who call it (friends in Oklahoma told me) the “F” word.